2018
DOI: 10.3847/1538-3881/aae83a
|View full text |Cite
|
Sign up to set email alerts
|

Limits on Clouds and Hazes for the TRAPPIST-1 Planets

Abstract: The TRAPPIST-1 planetary system is an excellent candidate for study of the evolution and habitability of M-dwarf hosted planets. Transmission spectroscopy observations performed on the system with the Hubble Space Telescope (HST) suggest that the innermost five planets do not possess clear hydrogen atmospheres. Here we reassess these conclusions with recently updated mass constraints. Additionally, we expand the analysis to include limits on metallicity, cloud top pressure, and the strength of haze scattering.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 80 publications
(147 reference statements)
1
67
0
Order By: Relevance
“…No prominent absorption features at near-infrared wavelengths in the transmission spectra of the atmospheres of the TRAPPIST-1 planets rule out cloud-free, hydrogen-rich atmospheres (de Wit et al 2016(de Wit et al , 2018Zhang et al 2018;Burdanov et al 2019), whereas a clear hydrogen-rich atmosphere for TRAPPIST-1 f and 1 g is still in dispute (de Wit et al 2018;Moran et al 2018;Wakeford et al 2019). Our results show that all the TRAPPIST-1 planets used to have a hydrogen-rich atmosphere of 10 −2 − 1 wt% just after disk dispersal.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…No prominent absorption features at near-infrared wavelengths in the transmission spectra of the atmospheres of the TRAPPIST-1 planets rule out cloud-free, hydrogen-rich atmospheres (de Wit et al 2016(de Wit et al , 2018Zhang et al 2018;Burdanov et al 2019), whereas a clear hydrogen-rich atmosphere for TRAPPIST-1 f and 1 g is still in dispute (de Wit et al 2018;Moran et al 2018;Wakeford et al 2019). Our results show that all the TRAPPIST-1 planets used to have a hydrogen-rich atmosphere of 10 −2 − 1 wt% just after disk dispersal.…”
Section: Discussionmentioning
confidence: 59%
“…The combined spectrum of the planets rules out cloud-free, hydrogen-dominated atmospheres, except for TRAPPIST-1 f and 1 g (de Wit et al 2018;Moran et al 2018); Wakeford et al (2019) recently suggested that a clear hydrogen-dominated atmosphere may be ruled out for TRAPPIST-1 g. Since high-altitude clouds and haze are not expected to form in hydrogen-dominated atmospheres around temperate planets (e.g. Morley et al 2015), transit spectroscopy of the TRAPPIST-1 planets suggests no atmosphere or a high-metallicity atmosphere referred to as a secondary atmosphere.…”
Section: Introductionmentioning
confidence: 98%
“…We simulate the transmission spectra for R = 300 from 0.6−5.3 µm relevant for the NIRSpec/PRISM instrument on JWST, which has been shown to be the ideal instrument for JWST characterization of terrestrial exoplanets (Batalha et al 2018. We use the PSG imager noise model and do not include a noise floor in our simulated spectra.…”
Section: Simulated Observablesmentioning
confidence: 99%
“…Transits from seven small rocky planets on short period orbits were found, allowing detailed studies to be conducted on the possible atmospheres and their constituents of small planets orbiting a single star, and hence with similar initial conditions (e.g. Alberti et al 2017;Ducrot et al 2018;Moran et al 2018;Miles-Páez et al 2019;Burdanov et al 2019).…”
Section: Introductionmentioning
confidence: 99%